Mal de Río Cuarto Virus Infection Triggers the Production of Distinctive Viral-Derived siRNA Profiles in Wheat and Its Planthopper Vector - de Haro, Luis A.; Dumón, Analía D.; Mattio, María F.; Argüello Caro, Evangelina Beatriz; Llauger, Gabriela; Zavallo, Diego; Blanc, Hervé; Mongelli, Vanesa C.; Truol, Graciela; Saleh, María-Carla; Asurmendi, Sebastián; del Vas, Mariana (Frontiers in Plant Science, 2017)
Plant reoviruses are able to multiply in gramineae plants and delphacid vectors encountering different defense strategies with unique features. This study aims to comparatively assess alterations of small RNA populations in both hosts upon virus infection. For this purpose, we characterized the small RNA profiles of wheat and planthopper vectors infected by Mal de Río Cuarto virus (MRCV, Fijivirus, Reoviridae) and quantified virus genome segments by RT-qPCR. We provide evidence that plant and insect silencing machineries differentially recognize the viral genome, thus giving rise to distinct profiles of virus-derived small interfering RNAs (vsiRNAs). In plants, most of the virus genome segments were targeted preferentially within their upstream sequences and vsiRNAs mapped with higher density to the smaller genome segments than to the medium or larger ones. This tendency, however, was not observed in insects. In both hosts, vsiRNAs were equally derived from sense and antisense RNA strands and the differences in vsiRNAs accumulation did not correlate with mRNAs accumulation. We also established that the piwi-interacting RNA (piRNA) pathway was active in the delphacid vector but, contrary to what is observed in virus-infected mosquitoes, virus-specific piRNAs were not detected. This work contributes to the understanding of the silencing response in insect and plant hosts.